2019
DOI: 10.33338/ef.84482
|View full text |Cite
|
Sign up to set email alerts
|

Association between land cover and <i>Culicoides</i> (Diptera: Ceratopogonidae) breeding sites on four Danish cattle farms

Abstract: Bitingmidges of the genus Culicoides are vectors of bluetongue virus. Their larval habitats are poorly known in Northern Europe. Three classes of the CORINE land cover index, found within 300 m of four farms in Denmark, were used to stratify sampling sites for a total of 360 soil core samples from 30 sampling points. Soil samples were set up in emergence chambers for hatching adult Culicoides. Two species of Culicoides (C. punctatus and C. pulicaris) emerged from nine of 12 soil samples froma wet, grazed field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In addition, proximity to features such as water bodies or damp ground can affect vector community and density. Areas near standing water are often important for determining prevalence of Plasmodium , which is most frequently mosquito‐borne (Wood et al, ), whereas damp and marshy ground is more important for parasites vectored by Culicoides midges, the primary vectors of Haemoproteus (Kirkeby, Bødker, Stockmarr, & Enøe, ). However, a recent study of Amazonian birds did not find such a relationship (Pulgarín‐R et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, proximity to features such as water bodies or damp ground can affect vector community and density. Areas near standing water are often important for determining prevalence of Plasmodium , which is most frequently mosquito‐borne (Wood et al, ), whereas damp and marshy ground is more important for parasites vectored by Culicoides midges, the primary vectors of Haemoproteus (Kirkeby, Bødker, Stockmarr, & Enøe, ). However, a recent study of Amazonian birds did not find such a relationship (Pulgarín‐R et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…more important for parasites vectored by Culicoides midges, the primary vectors of Haemoproteus(Kirkeby, Bødker, Stockmarr, & Enøe, 2009). However, a recent study of Amazonian birds did not find such a relationship(Pulgarín-R et al, 2018).…”
mentioning
confidence: 99%
“…This may be a problem of insufficient data resolution: even the CORINE land cover index, a dataset of finer spatial resolution than the Climate Change Initiative Land Cover used here, cannot accurately predict Culicoides spp. breeding sites [83]. Thus, high-resolution remote sensing might be required to improve the performance of land cover variables for Culicoides spp.…”
Section: Culicoides Spp Distribution Modelsmentioning
confidence: 99%
“…Dispersal studies using mark-release-recapture technique suggested possible dispersal distance of 1.75 km per 24 h in Denmark and of 1.50 km per 24 h in the UK (Kluiters et al, 2008;Kirkeby et al, 2009). The flight altitude was assessed by Sanders et al (2011a) in the UK recording adult biting midges at 200 m above land using a tethered balloon.…”
Section: Hours Of Attack and Dispersalmentioning
confidence: 99%
“…Breeding habitats of other species such as C. pulicaris has been found in soil samples from grazed field with manure in Denmark (Kirkeby et al., ).…”
Section: Assessmentmentioning
confidence: 99%